FAPSO: Fast Adaptive Particle Swarm Optimization-Based Background Timing Skew Calibration for TI-ADCs - Wang, Longsheng; Li, Dengquan; Ding, Ruixue; Zhu, Zhangming (IEEE transactions on circuits and systems. I, Regular papers, 2024)
This article presents a background calibration method for timing skew in time-interleaved (TI) analog-to-digital converters (ADCs). The proposed algorithm employs fast adaptive particle swarm optimization (FAPSO) to detect the timing skews in sub-channels and compensates them using second-order finite impulse response (FIR) differentiators. This approach enables simultaneous convergence of each channel and reduces the convergence time significantly. Hardware implementation of the proposed timing skew calibration is synthesized by field-programmable gate array (FPGA), and it consumes a total power of 7.3 mW. The effectiveness of the proposed FAPSO algorithm is verified through a commercial 12-bit 3.6-GS/s 4-channel TI-ADC. After applying FAPSO timing skew calibration, the signal-to-noise and distortion ratio (SNDR) and spurious-free dynamic range (SFDR) are improved by 16.5 and 29.6 dB, respectively.